(untitled) (REMUNOM, 2025)
The belief that the phases of the moon influence different aspects of animal and plant life is an ancient tradition that persists in popular culture. In the context of horse breeding, many breeders believe that the moon plays a significant role in the timing of the birth of foals. This article demonstrates the influence of the moon on the birth of 143 foals from 4 different stud farms in the Paraíba Valley region of the State of São Paulo, in the cities of Taubaté and Pindamonhangaba. It also demonstrates the influence of the moon on the sex of foals, analyzing evidence that supports or refutes this belief.